Fatal multiple organ failure in an adolescent due to community-acquired methicillin-susceptible Staphylococcus aureus ST121/agrIV lineage. Issue 4 (November 2015) - Rao, Qing; Shang, Weilong; Zhou, Kun; Zhou, Renjie; Rao, Xiancai
<x xml:space="preserve">Abstract</x> Adolescent deaths due to Staphylococcus aureus infection are rare. We describe the case of a 17-year-old boy who died from septic multiple organ failure caused by community-acquired methicillin-susceptible S. aureus. The patient's first clinical symptom was a skin and soft tissue infection, with multiple organ failure developing 5 days afterwards. The causative organism S. aureus was further determined to carry Panton-Valentine leukocidin genes, and molecularly characterized as staphylococcal protein A (spa) type t159, multilocus sequence type (ST)121, and accessory gene regular (agr) type IV. ST121/agrIV S. aureus is one of the minor lineages prevailing in China, and this is the first fatal case reported due to ST121/agrIV lineage of community-acquired methicillin-susceptible S. aureus in the country.